Case report: Effectiveness of sirolimus in treating partial DiGeorge Syndrome with Autoimmune Lymphoproliferative Syndrome (ALPS)-like features - Gu, Hao; Mou, Wenjun; Chen, Zhenping; Xie, Xingjuan; Yao, Jiafeng; Zhang, Rui; Wu, Runhui; Gui, Jingang (Frontiers in Pediatrics, 2023)
Background DiGeorge Syndrome (DGS) is a rare disease associated with 22q11.2 chromosomal microdeletion, also known as a velocardiofacial syndrome, based on the frequent involvements of the palate, facial, and heart problems. Hematologic autoimmunity is rare in DGS but presents with a refractory course and poor prognosis. Herein, we report a case of partial DGS in a patient with refractory immune cytopenia and autoimmune lymphoproliferative syndrome (ALPS)-like manifestations. Case description A 10-year-old boy with growth retardation presented initially with a ventricular septal defect at 7 months old, which had been repaired soon after. The patient suffered from thrombocytopenia and progressed into chronic refractory immune thrombocytopenia (ITP) at 30 months old. One year later, the patient developed multilineage cytopenias including thrombocytopenia, neutropenia, and anemia. First-line treatment of ITP, like high-dose dexamethasone and intravenous immunoglobulin, had little or short-term effect on controlling symptoms. Whole-exome sequencing revealed the presence of a de novo heterozygous 2.520 Mb deletion on chromosome 22q11.21. Moreover, decreased proportion of naive T cells and elevated double-negative T cells were found. The patient was given sirolimus therapy (1.5 mg/m2, actual blood concentration range: 4.0–5.2 ng/ml) without adding other immunosuppressive agents. The whole blood cell count was gradually restored after a month, and the disease severity was soothed with less frequency of infections and bleeding events. Decreased spleen size and restrained lymph node expansion were achieved after 3-month sirolimus monotherapy. Conclusions This case is the first description on the efficacy of sirolimus monotherapy to treat refractory multilineage cytopenias of DGS presented with ALPS-like features.